2015
DOI: 10.1111/obr.12325
|View full text |Cite
|
Sign up to set email alerts
|

Fat, sugar and water intakes among families from the IDEFICS intervention and control groups: first observations from I.Family

Abstract: This result indicates better diet quality in intervention families, which was not present in children when their diets were assessed before the intervention, and gives some cause for optimism regarding the sustainability of some aspects of the diet intervention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 40 publications
(53 reference statements)
2
21
0
Order By: Relevance
“…Figure describes the search results – 33 interventions were entered into the data corpus as meeting all inclusion criteria. Each intervention took place across multiple community settings and focused on systems change to promote healthy behaviours at the individual level applying a range of study designs . The interventions were participatory in nature, with a foundational component built on community engagement, empowerment and capacity building.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure describes the search results – 33 interventions were entered into the data corpus as meeting all inclusion criteria. Each intervention took place across multiple community settings and focused on systems change to promote healthy behaviours at the individual level applying a range of study designs . The interventions were participatory in nature, with a foundational component built on community engagement, empowerment and capacity building.…”
Section: Resultsmentioning
confidence: 99%
“…Schools were the primary setting for data collection in 29 of 33 interventions , and barriers around recruiting, engaging and following up with schools were frequently reported . Logistically, working around school timetables and vacation periods proved challenging , and one intervention noted that several visits to schools were often necessary to re‐measure all participants in the follow‐up period .…”
Section: Resultsmentioning
confidence: 99%
“…This finding could be an example of information dissemination paradox or ‘boomerang’ effect , reactive responses in which people might reject or doubt the relevance of information received. Other potential explanations for the outcome based on parental views on the intervention process and on data collected in the extended follow‐up of these families 5 years after the intervention will be considered in future country‐specific analyses.…”
Section: Resultsmentioning
confidence: 99%
“…Two years after baseline, post‐intervention examinations including anthropometric measurements were conducted in the majority of participating children. Results documenting the effect of the intervention on body mass index (BMI) , describing parental approval of the intervention , and examining longer‐term differences between dietary habits of families in intervention versus control regions are reported separately in this supplement. The present analysis explores whether there is a differential intervention outcome in children with and without prevalent OWOB.…”
Section: Methodsmentioning
confidence: 99%
“…In spite of high expectations, the IDEFICS trial did not accomplish its primary objectives of mitigating or reversing the substantial increases in child obesity in Europe after 2 years of intervention . The IDEFICS intervention similarly did not impact the 2‐year energy balance‐related behaviours of dietary intake , physical activity, physical inactivity or sleep , although an analysis 5 years after the intervention suggested that the intervention might have had an impact on water and sugar consumption . Without such behavioural or adiposity effects, it was not surprising that the IDEFICS trial had no impact on insulin resistance or markers of the metabolic syndrome .…”
Section: Critical Appraisal Of the Overall Resultsmentioning
confidence: 99%